Differention and activation marker of lymphocyte of peripheral blood of patients with malignant ephithelial tumours of skin of eyelids (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Important role in the onset and progression of the tumor process plays the immune system, normal function of which is the recognition of tumor rejection cells. In some cases, the tumor is not only loses sensitivity to inhibit the action of the immune system, but also gains the ability to use it to stimulate growth factors. For proteins able to regulate immune mechanisms and act as tumor factors care immunological monitoring include membrane antigens of immune system cells: CD3 +, CD4 +, CD8 +, CD16 +, CD19 +, CD25 + and CD95 +. Violation of their equilibrium in biological fluids leads to modulation of cell-cell membrane interactions and the immune response respectively.Purpose. Define informative expression of differentiation (CD3 +, CD4 +, CD8 +, CD16 + CD19 +) and activation ( CD25 +, CD95 +) lymphocyte markers in the peripheral blood of patients with malignant epithelial tumors (MET) of the eyelid skin without relapse and recurrence of cancer. Material and methods. The study was conducted in 165patients with MET eyelid skin stage T2a -3b N0 M0. Men were 74 (44.8 %), women — 91 (55.2 %). The median age (63,5±11,7) years. Control group consisted of 28 apparently healthy individuals aged (64,0±9,91) years, there were 12 men ( 46.4 %), women — 16 (53.6 %). Phenotypic composition of peripheral blood lymphocyte Theo age was assessed using specific McAB panel (CD3 +, CD4 +, CD8 +, CD16 +, CD19 +, CD25, CD95).Results. Absolute and relative abundance of CD3 +, CD4 + and CD8 + in peripheral blood of patients with MET eyelid skin as in the group without recurrence, and with tumor recurrence were observed. With respect to the norm, these figures were significantly lower (p = 0.000). In the group without recurrence expression levels (CD3 +) were below normal respectively, 1,5 and 1,2 -fold, and relapse — 1,8 and 1,3 times. Indicators expression (CD4 +) in the test groups were lower in controls 2,0 and 1,3 -fold (p = 0.000). CD8 + expression in both groups compared to the control is reduced and respectively, 1,3 and 1,7 times (p1 = 0.005, p2 = 0.000). Significantly lower in absolute figures CD16 + relative to 1,4 times normal in patients with relapses (p = 0.001). Expression of CD25 + group with tumor recurrence in 1,3 and 1,5 times higher than in the group without relapses. For CD95 + group with tumor recurrence are 1,6 and,.2 times lower than in the group without relapse. The expression level of CD25 + and CD95 + in both groups was significantly higher than controls (p = 0.000).Conclusion. Patients with MET eyelid skin reduced cellular immunity by reducing (CD3 +, CD4 +, CD8 +) lymphocytes. Increased content of activation (CD25 +, CD95 +) lymphocytes. When relapse — broken nonspecific mechanism of immune surveillance by reducing antigen (CD16 +), develops unresponsiveness of T- cells by increasing antigen (CD25 +) and the induction of Fas -mediated apoptosis of lymphocytes responsible for the formation of tumor immunity by antigen (CD95 +).
Keywords: malignant epithelial tumors of the eyelid skin; recurrence; immunolologic status; markers lymphocytes (CD3 +, CD4 +, CD8 +, CD16 +, CD19 +, CD25, CD95)